KEMAMPUAN MENULIS KREATIF NASKAH DRAMA DENGAN PENGGUNAAN PENDEKATAN KONTEKSTUAL TIPE LEARNING COMMUNITY KELAS VIII SMP NEGERI 9 PADANGSIDIMPUAN - Paisal, Hendry (UNIB Press, 2021)
Writing literary works is one of the main subjects in Indonesian language lessons in every school, including the Special School. Therefore, teachers who teach Indonesian language lessons should understand and master the provisions that apply in writing literary works, be it short stories, novels, dramas, and poetry. Learning with a contextual approach to the type of learning community is the latest learning compared to other models. This learning emphasizes students' creativity in argumentation, appreciation, and assessment. The goal is to generate personal interaction both individually and in groups through discussion. So this study aims to reveal the ability of students to write drama scripts using a contextual approach of learning community type, especially in class VIII SMP N Padang Sidimpuan.